Strategies of Removing Residual Lithium Compounds on the Surface of Ni‐Rich Cathode Materials†. Issue 1 (23rd December 2020) - Su, Yuefeng; Li, Linwei; Chen, Gang; Chen, Lai; Li, Ning; Lu, Yun; Bao, Liying; Chen, Shi; Wu, Feng
Abstract: Ni‐rich cathode materials have become one of the most promising cathode materials for advanced high‐energy Li‐ion batteries (LIBs) owing to their high specific capacity. However, Ni‐rich cathode materials are sensitive to the trace H2 O and CO2 in the air, and tend to react with them to generate LiOH and Li2 CO3 at the particle surface region (named residual lithium compounds, labeled as RLCs). The RLCs will deteriorate the comprehensive performances of Ni‐rich cathode materials and make trouble in the subsequent manufacturing process of electrode, including causing low initial coulombic efficiency and poor storage property, bringing about potential safety hazards, and gelatinizing the electrode slurry. Therefore, it is of considerable significance to remove the RLCs. Researchers have done a lot of work on the corresponding field, such as exploring the formation mechanism and elimination methods. This paper investigates the origin of the surface residual lithium compounds on Ni‐rich cathode materials, analyzes their adverse effects on the performance and the subsequent electrode production process, and summarizes various kinds of feasible methods for removing the RLCs. Finally, we propose a new research direction of eliminating the lithium residuals after comparing and summing up the above. We hope this work can provide a reference for alleviating the adverse effects of residual lithium compounds for Ni‐rich cathode materials' industrial production. Abstract :